2018
DOI: 10.1097/qai.0000000000001720
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of HIV Care in Rural Mozambique: The Implications of HIV Testing Modality on Linkage and Retention

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 38 publications
(42 reference statements)
4
54
1
Order By: Relevance
“…Prior to the current study and in order to exclude non-eligible participants, a standard deterministic and probabilistic record-linkage [20], validated by other studies [21,22], was conducted to match individuals from the cross-sectional community-based serosurveys and the Manhiça District Hospital ePTS (MDH-ePTS) to identify individuals who were already known HIV-positive at the time of the 2010 and 2012 serosurveys.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the current study and in order to exclude non-eligible participants, a standard deterministic and probabilistic record-linkage [20], validated by other studies [21,22], was conducted to match individuals from the cross-sectional community-based serosurveys and the Manhiça District Hospital ePTS (MDH-ePTS) to identify individuals who were already known HIV-positive at the time of the 2010 and 2012 serosurveys.…”
Section: Methodsmentioning
confidence: 99%
“…Also, participants working at baseline were more likely to be retained at 6-month follow-up compared to unemployed participants, although no significant associations were found for 12-month follow-up and for those attending both follow-up appointments. Other studies have found that working is associated with higher attrition rates, probably as a result of inflexible work schedules 19 , 28 , 50 , 51 . However, some authors have found opposite results, with lack of formal employment being a barrier to retention 33 , 52 .…”
Section: Discussionmentioning
confidence: 94%
“…The importance of providing effective linkage services is underscored by over 15 studies in sub‐Saharan Africa, including one in Mozambique, suggesting that only 18%‐51% of PLHIV diagnosed in community settings enrol early in HIV care when referral is the only linkage service [ 10 , 27 , 28 , 29 ]. Among all PLHIV aged 15 to 59 years in CHDSS, however, ART coverage increased from 65% in R1 to 88% in R5, and viral load suppression coverage increased from 52% in R1 to 78% in R5 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%